STRATEGI PEMBELAJARAN UNTUK MENGAKTIFKAN PROSES BERPIKIR KRITIS DALAM PEMBELAJARAN BAHASA INDONESIA - Neneng Ratnadila; Aditya Ibrahim; Ariyana (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This study aims to determine effective and efficient learning strategies that can be applied by teachers to students to help activate students' critical thinking processes in learning Indonesian, especially to improve language skills, namely reading, writing, listening and speaking. Critical thinking skills are one of the skills that must be possessed in the era of technological advancement like today. The research conducted uses a qualitative descriptive approach to present data in the form of written descriptions of the findings. The techniques used in this study are, reading, listening and recording conclusions obtained from various literature. The results of the research analysis presented are 1) an inquiry learning model to improve listening skills, 2) a project-based learning model to increase writing productivity, 3) a problem-based learning model to improve speaking skills and 4) a discovery learning model in optimizing reading skills. Keywords: Learning Strategy; Critical Thinking; Bahasa Indonesia